Perbedaan Pengaruh Penggunaan Transtibial Prosthesis Dan Axial Crutch Terhadap Keseimbangan Pasien Post Amputasi Transtibial - Nur Rachmat; Alfan Zubaidi (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Transtibial Prosthesis, Walking Balance, Axilla Crutch, Post Transtibial Amputation. This study aims to determine the effect of the use of transtibial prosthesis and axial crutch on the balance of transtibial post amputation patient. This research is hoped to be beneficial to the benefit of people who have transtibial amputation in order to obtain the appropriate balance. This research method is Quantitative research, pre experiment, using research design one groups pre and post test design, where in this research there is only one group of subjects that will be measured equilibrium using prosthesis and axial crutch. Research conducted at PT. Kuspito Ortotik Prostetik. In this research, there are two variables, namely (1) dependent variable, balance, (2) independent variables are use of transtibial prosthesis and axial crutch. Data collection is done in two stages, first and second phase. In the first stage, the researcher records the client identity that has been defined as the research subject (sample), including name, gender, age, address, and examination to establish the type of patient who meets the inclusion criteria. Afterwards, measurements were made on patients using transtibial prostheses and recording the results of the treatment group in terms of their equilibrium values. In the second stage of data collection, measurements were taken in patients using axial crutch and recording the results of the treatment group in terms of their equilibrium value. The instruments used are TUG Test equipment (armrest and armrest seats, stopwatch, wall, stationery). Data were analyzed with SPSS for Win13.00 for Windows software. Test the normality of data using Shapiro-Wilk normality test. The results showed that there was a difference of effect of axial crutch with prosthesis on post amputation patient equilibrium (0,017 <0,05), it is also known that average equilibrium in group of axial crutch (18,46) while mean balance in group Prosthesis (20,84). Crutches are walking sticks, usually used in pairs that are created to regulate the balance at the time of going and sustaining the user's body. Axilla crutches are not designed to rest during support of the body. To minimize the inconvenience of using axilla crutches, a prosthesis is created which, when an amputation patient has been determined to use a prosthesis, determines the purpose of prosthetic fitting, whether functional, cosmetic or both.